The Right to Protection of Private and Family Life Under Article 8 of the ECHR. Cases Related to a Request to Change the Name, Gender and Data in Identity Documents and Population Registers - Djarova, Dessislava (Yearbook of the Law Department, 2022)
The article examines cases of incorrect case-law on the application of article 8 of the ECHR. Particular attention is paid to the reasons why in Bulgaria has been established controversial case-law on the recognition of the gender identity of persons with different sexual orientation or on the recognition of marriage between same-sex couples in another country. The article focuses on the dissenting opinions expressed by judges of the Constitutional Court on the interpretation of the concept of “gender” and on the dissenting opinions of judges of the Supreme Court of Cassation in cases aimed at ensuring recognition and protection of the right to private and family life of persons with different sexual orientation. Ignoring the judgments against Bulgaria constitutes, in respect of persons of different sexual orientation, a state inaction, which negatively affects their legal sphere.